5G New Radio Key Performance Indicators Evaluation for IMT-2020 Radio Interface Technology - A. Phani Kumar Reddy (IEEE, 2021)
The International Telecommunication Union (ITU) has recently announced the detailed 5G specifications for International Mobile Telecommunications (IMT-2020). A number of candidate Radio Interface Technologies (RITs) were being evaluated by the independent evaluation groups of the ITU. Meanwhile, the roll out of fifth generation (5G) is now going on, and 5G services are offered by more than 160 mobile network operators (MNO). This paper presents the evaluation of the proponent technologies, including the ones specified as $3^{\text {rd}}$ generation partnership project (3GPP) 5G new radio (NR). The entire 3GPP specifications were examined and evaluated through simulation using Matlab and a custom simulator based on the Go-language. The simulator facilitated the comprehensive evaluation of the 5G NR performance by using the IMT-2020 evaluation framework. Some of the submitted technologies displayed certain discrepancies which were reported to ITU as well as discussed with proponents to improvise the shortcomings. The detailed results and observations are presented in this paper.